Dynamic Plastic Deformation Induced by Repetitive Hammering on Cr-Mn Austenitic Stainless Steel - Syahwira Taqwa Triadi; Cherly Selindiana; Hermawan Judawisastra; Aditianto Ramelan; Rochim Suratman (Metalurgi, 2022)
Austenitic stainless steels have advantages, such as high ductility and good corrosion resistance. The cold working process can increase the hardness and strength of the material. However, because a metastable austenite phase occurs in that material, there is a phase change of γ austenite to α’-martensite and ε-martensite, which will reduce the ductility and its corrosion resistance. The strengthening process with dynamic plastic deformation (DPD) can prevent the formation of martensitic phases through repeated impact at high strain rates. This study analyzed microstructures and hardness evaluation on Cr-Mn austenitic stainless steel due to dynamic plastic deformation through the repetitive hammering method. Repetitive hammering with a strain rate of 6,2 s-1 on Cr-Mn austenitic stainless steels was carried out on five specimens with variations in the impact of 50, 100, 150, 250, and 350 times with impact energy of 486 J/cm2, 2.207 J/cm2, 2.569 J/cm2, 6.070 J/cm2, and 11.330 J/cm2 respectively. Microstructure, hardness, and XRD (X-ray diffraction) analyses were carried out on specimens before and after repetitive hammering. Metallography was carried out to observe the microstructure using an optical microscope. The hardness was tested through the Rockwell A hardness test. XRD examination was used to identify the phases formed and indications of nano-twins. The repetitive hammering process up to 350 times has succeeded in increasing hardness from 53.5 HRA to 71.6 HRA. Plastic deformation introduced by repetitive hammering produced slip bands, cross bands, wavy bands, and indication of nano-twins formation and increased the hardness.